ANALISIS PELAKSANAAN PEMBELAJARAN SOSIOLOGI MODEL PBL BERBANTUAN VIDEO SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR ANALITIS SISWA KELAS XI SOSIOLOGI 4 MAN 2 PONTIANAK - Renada, Ajiza; Warneri, Warneri; Ramadhan, Iwan (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2026)
The objective of this study is to examine the outcomes of implementing video-based Problem-Based Learning (PBL) in sociology instruction as an effort to enhance the analytical thinking skills of Grade XI Sociology 4 students at MAN 2 Pontianak. The research employed a descriptive qualitative method. Data collection techniques included observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data presentation, and conclusion drawing. The analysis was conducted using information from seven informants. The findings indicate that (1) In the aspect of distinguishing problems, most students were able to understand the issues presented in the video, separate essential information, and differentiate elements of the conflict, such as causes, consequences, and perspectives of the parties involved. Moreover, students’ engagement and enthusiasm in the learning process also increased. (2) In the aspect of organizing problems, students were able to present information from the video in a structured manner, compile the viewpoints of various parties involved in the conflict, and arrange causes and consequences into a logical sequence. (3) In the aspect of connecting problems, students were able to relate the conflict to the theories studied and provide analytically sound and realistic solutions to the problems. This study describes the outcomes of implementing video-based PBL as an effort to enhance the analytical thinking skills of Grade XI Sociology 4 students at MAN 2 Pontianak. In this context, analytical thinking is categorized into three aspects: distinguishing, organizing, and connecting.